Mechanical Properties of Oil Palm Empty Fruit Bunch (EFB) - High Density Polyethene (HDPE): Influence OfProcessing Techniques - Muhamad Yunos, Muhamad Aizat (Universiti Teknologi PETRONAS, 2009)
The objective of the project is to investigate the effects of varying processing techniques on tensile properties and flexural properties of empty fruit bunch (EFB) - high density polyethylene (HDPE) composites. Dried empty fruit bunch fiber of5 mm in length was compounded with HDPE matrix using extruder machine at 150°C. The resulting compound is further processed using either an injection molding or compression molding to obtain the tensile test bars. Samples obtained from both processing techniques were subjected to tensile test and flexural test. Finally, the tensile properties and flexural properties obtained from both processing techniques were analyzed and compared. The samples from injection molding process exhibited better tensile properties and flexural properties compared to those fabricated using compression molding. This was due to pore spaces or voids within the compression molding samples. Furthermore, the voids between the EFB fibers and HDPE matrix could also be the reason for poor mechanical properties of both injection molded and compression molded samples. The effect of EFB fiber were negligible in tensile test, but it shown a large significant in flexural strength as the percentage difference of flexural strength and flexural modulus showed the highest in each properties with value of 31% and 30%. These results indicate that processing technique does have an influence on the mechanical properties of the EFB-HDPE composites. n